Semantic relation computing theory and its application. (January 2016) - Sun, Yunchuan; Lu, Cheng; Bie, Rongfang; Zhang, Junsheng
Abstract: Semantic relations among objects are primary semantic factors, which play the most important role for human and smart systems /machines to understand and control the situation in the context of connected systems. However, few existing works focus on the study of semantic relations from the mathematical view, though it would be the basis for further research on semantics. Existing research works focus on the representation of semantic relations and reasoning with relations, but seldom concentrate on the semantic relation computing including accurate reasoning, integrity checking and redundancy checking. In this paper, we aim at exploring algebraic computing approach of semantic relations. A mathematical computing theory for establishing semantic relations – semantic relation space theory – is proposed for the first time, including conceptions of semantic relation basis, orthogonal basis, and some basic operations for semantic relations. The proposed theory can be used to represent the semantic relations among objects in an accurate way and to deduce implicit relations in the connected smart systems, especially for automatic reasoning and autonomous computing. Furthermore, integrity and consistency issues among semantic relations are also discussed based on the theory. A case study in scientific research domain has shown the feasibility and effectiveness of the proposed theory.